Experimental cultivation of the South African scallop Pecten sulcicostatus - Arendse, Dale Cheryle (Department of Biological Sciences, 2016)
Although scallops have a high economic value, they have yet to be commercially harvested or farmed in South Africa. Of the 29 Pectinid species recorded on the southern African coastline, Pecten sulcicostatus is the only species considered suitable for aquaculture, due to its large size. An investigation of the suitability of P. sulcicostatus for farming in South Africa forms the basis of this study. The successful cultivation of P. sulcicostatus will depend on successful rearing from fertilized egg to market size, and achieving a growth rate comparable to that of other commercial scallop species. This study aimed to examine the reproductive life cycle, in order to establish whether this species can be artificially conditioned to produce ripe gametes throughout the year and to investigate the various stages of cultivation, in order to determine whether this species is viable for farming. This thesis therefore describes the reproductive cycle of P. sulcicostatus and also reports on the first assessment of broodstock conditioning, larval rearing and the grow-out of spat. The reproductive study was undertaken by monthly collection of scallops in their natural habitat in False Bay from August 2004 - October 2005 and again from August 2010 - August 2011. The reproductive cycle was assessed by means of both gonadosomatic index (GSI) and qualitative and quantitative histological investigation. Environmental parameters were also monitored to determine any linkage to the reproductive cycle. The reproductive cycle was seasonal, with a peak spawning period in winter. A resting period appeared absent, as individuals started producing new gametes immediately after spawning, indicating a possible lack of synchronicity.